The Effects of Injectable Trace Elements on Metabolic Parameters in Transition Cow - Avci, Cem; Kizil, Omer (Kafkas Univ, Veteriner Fakultesi Dergisi, 2013)
The aim of this study was to determine the effects of mineral administration on metabolic profiles in the cows during transition period. Twenty healthy pregnant cows under the same care and feeding conditions were used in the study. The animals were divided into two equal groups including 10 animals in each. The trace mineral injection was administered to the experimental group intramuscularly (20 ml/cow) on the beginning of the transition period. 20 ml isotonic sodium chloride was injected subcutaneously on beginning of the transition period in the control group as placebo. Blood samples were taken by venipuncture of the jugular vein on beginning of the transition period, parturition time and three after parturition, respectively. The NEFA, BHBA, albumin, glucose, T. cholesterol, VLDL-cholesterol, LDL-cholesterol, HDL-cholesterol, triglyceride, AST, ALT, GGT, T. bilirubin, creatinine, BUN and T. protein levels were determined in the both groups as metabolic parameters. In conclusion, the mineral solution particularly contains selenium, copper, zinc and manganese that administrated on beginning of the transition period could be effective on metabolic parameters.
Enjektabl i?z elementlerin geçiş dönemindeki i?neklerde metabolik profil üzerine etkileri
Keywords: Transition period; Cow; Metabolic profile; Trace element